Composition of regional conditions for start-up activity- evidence based on Swiss Mobilite Spatiale regions - Franz Kronthaler; Katharina Becker; Kerstin Wagner (European Regional Science Association (ERSA), 2010)
Start-up activities are considered to be important for regional economic development and vary considerably between regions. As entrepreneurial activity in a region is strongly influenced by its regional conditions, we analyse the role of the conditions and their impact on start-up activities. The main objective of the paper is to identify the variables which are relevant for a typology of regions in terms of their start-up activity and to have a closer look on their region specific characteristics. For the analysis we use the spatial level of Swiss mobilité spatiale regions (MS). MS regions are functional units based on economic interaction and commuting movements. At this level, data is available which provide information about the endogenous entrepreneurial potential of regions. Furthermore, it is possible to distinguish between peripheral, semi-peripheral, urban regions and agglomerations. Cluster analysis and regression analysis are used to examine the relationship between regional conditions as influencing factors and real start-up rates. The selection of the indicators is based on a review of results of the theoretical and empirical literature on entrepreneurship. Cluster Analysis serves to compare different regions according to their structural potential for start-up activities. The method is used to form several homogeneous groups of Swiss labour market regions according to their individual structural potential and for comparative purposes. With the help of regression analysis we analyze whether the different types of cluster really explain start-up activity and if obstacles for entrepreneurial activity can be found. Results indicate that most of the regions use their potential for entrepreneurial activity. However, we also identify certain outliers with regard to the relationship of regional conditions and start-up activity. On the one hand, we observe regions with good structural conditions and high potential for new firm formation but low start-up rates. On the other hand, there are regions with unfavorable characteristics but relatively high start-up rates. Based on this analysis, we identify case specific variables influencing start-up activities under specific circumstances. These regions are potentially interesting cases for constructing regional policies.
Keywords: R11; R58; L26; 330; Regional Economics; Entrepreneurship; Business Formation